Microwave Effects on Microstructure of Ceramics - Sudianaa, I Nyoman Sudianaa; Mitsudob, Seitaro; Inagakib, Shunsuke; Sakob, Katsuide (Majalah Ilmiah Pendidikan Matematika dan Ilmu Pengetahuan Alam, 2014)
The sintering and microstructure evolution of alumina ceramic sintered by a wide range microwave were investigated. Bulk density were calculated by using Archimedes method while the grain size measurements were used to correlate sintering with grain growth was observed by electron microscope. The microwave effects such as an enhancement of densification and shorter time of processing of microwaves compared to conventional case have been found and reported in previous paper. There was also showed microwave frequency dependency of alumina`s densification.  Unfortunately there is no satisfactory theory to explain the phenomena. However the electric field inside sample during electromagnetic heating is believed as the main factor. In this paper further investigation of microwave effect on alumina properties was reported. The effect of microwave on microstructure of alumina is evaluated.  Grain evolution for each sintering methods were evaluated by using image processing on the scanning electron microscopy’s photos of fracture and grinded surfaces of samples. There showed that microstructure of sintered alumina is dependent on the microwave frequencies. Some possible mechanisms were also discussed.